Avaliação de um sistema indutivo para aquecimento de água para fins agroindustriais - Schlichting, Marcos Vinicius (2015)
This study evaluated a prototype for heating water for use in the agricultural industry, based on the principle of magnetic induction to generate thermal energy through the eddy currents associated with a mechanical energy source for variation of magnetic flux produced by permanent magnets, configured with four six magnets with and without pole reversal, as compared with the water heating done through a resistive system. Induced systems obtained yield 64.74%, 65.13% and 64.48% for six magnets without inversion (6ISI), four magnets with reverse (4ICI) and four magnets without inversion (4ISI) respectively. The resistive system showed 89.21% efficiency, demonstrating greater viability in the study conditions.